FGFR1 actionable mutations, molecular specificities, and outcome of adult midline gliomas. (5th June 2018) - Picca, Alberto; Berzero, Giulia; Bielle, Franck; Touat, Mehdi; Savatovsky, Julien; Polivka, Marc; Trisolini, Elena; Meunier, Sheida; Schmitt, Yohann; Idbaih, Ahmed; Hoang-Xuan, Khe; Delattre, Jean-Yves; et al.
Abstract : Objective: To characterize the prevalence and prognostic significance of major driver molecular alterations in adult midline diffuse gliomas (MLG). Methods: Adults with histologically proven MLG diagnosed between 1996 and 2017 were identified from our tumor bank, systematically reviewed, and reclassified according to WHO 2016. Targeted sequencing was performed, including determination of H3F3A, HIST1H3B, TERTp, IDH1/2, FGFR1, p16/CDKN2A, and EGFR status. Results: A total of 116 adult patients (M/F 71/45, median age 46.5 years) with MLG (17 cerebellar, 8 spinal, 30 brainstem, 57 thalamic, and 4 diencephalic nonthalamic) were identified. Most patients had high-grade disease at presentation (grade II: 11%, grade III: 15%, grade IV: 75%). Median overall survival was 17.3 months (14.5–23.8 months). Main molecular alterations observed were TERT promoter, H3F3A, and hotspot FGFR1 (N546 and K656) mutations, in 37%, 34%, and 18% of patients, respectively. IDH1 mutations only affected brainstem gliomas (6/24 vs 0/78; p = 7.5 × 10 −5 ), were mostly non-R132H (contrasting with hemispheric gliomas, p = 0.0001), and were associated with longer survival (54 vs 12 months). TERT promoter mutation (9.1 vs 24.2 months), CDKN2A deletion (9.9 vs 23.8 months), and EGFR amplification (4.3 vs 23.8 months) were associated with shorter survival. Of interest, in contrast with pediatric MLG, H3K27M mutations were not associated with worse prognosis (23 vs 15 months). Conclusions: Patients with adult MLG present with unique clinical and molecular characteristics, differing from their pediatric counterparts. The identification of potentially actionable FGFR1 mutations in a subset of adult MLG highlights the importance of comprehensive genomic analysis in this rare affection.